SONGS ABOUT GENIUNE LOVE: AURA OF CONSUMPTION IN CONTEMPORARY RUSSIAN POP MUSIC / ПЕСНИ О ВЕЩНОЙ ЛЮБВИ: АУРА ПОТРЕБЛЕНИЯ В СОВРЕМЕННОЙ РОССИЙСКОЙ ПОП-МУЗЫКЕ - ZHURKOVA D.A. / ЖУРКОВА Д.А. (Наука телевидения)
Popular product brands in songs of the modern domestic variety. Usually, their commercial component is not implied. This feature of the use of brands in the lyrics allows you to monitor the real contexts of consumption of various things, despite the inherent arbitrariness of the content of the songs. The author considers the model of the song characters ‘ relationship with the things of the constructed social status and the author’s attitude both: to the characters of the songs and to modern society.